Successful outcome of pregnancy in RHD with severe MS, severe pulmonary artery hypertension, moderate MR/TR/AR and mild AR - Rani, Anjali; Gupta, Prashanta Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Rheumatic heart disease with severe Pulmonary Arterial Hypertension (PAH) in pregnancy is a grave situation, present with high maternal morbidity and mortality. In this case report, we describe our successful management of such a case which was even more difficult in combination with sever mitral stenosis, severe pulmonary artery hypertension and mild to moderate MR/TR. This patient got her diagnosis late in pregnancy, beyond the time at which a therapeutic termination could not have been performed.